Evaluation of spray-dried wheat gluten as a component of calf starters - H. Terui; J. L. Morrill; M. Yashima (Kansas Agricultural Experiment Station Research Reports, 1993)
Holstein calves (n =52) were on experiment from birth to 10 wk of age. Control calves were fed starters containing soybean meal as the protein supplement. The other calves were fed starters in which part of the soybean meal was replaced by spraydried wheat gluten. Bull calves fed starters containing wheat gluten consumed more starter during the third and fourth week and gained more weight during the third week than control calves, but overall differences in weight gain or feed intake were not significant, nor was there a significant carryover effect when all calves were fed the same diet.; Dairy Day, 1993, Kansas State University, Manhattan, KS, 1993;
Keywords: Dairy Day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-149-S; Report of progress (Kansas Agricultural Experiment Station); 694; Dairy; Calves; Calf starters; Wheat gluten; Protein